Beyond allergic progression: From molecules to microbes as barrier modulators in the gut-lung axis functionality - Parrón-Ballesteros, Jorge; Gordo, Rubén García; López-Rodríguez, Juan Carlos; Olmo, Nieves; Villalba, Mayte; Batanero, Eva; Turnay, Javier (Frontiers in Allergy, 2023)
The “epithelial barrier hypothesis” states that a barrier dysfunction can result in allergy development due to tolerance breakdown. This barrier alteration may come from the direct contact of epithelial and immune cells with the allergens, and indirectly, through deleterious effects caused by environmental changes triggered by industrialization, pollution, and changes in the lifestyle. Apart from their protective role, epithelial cells can respond to external factors secreting IL-25 IL-33, and TSLP, provoking the activation of ILC2 cells and a Th2-biased response. Several environmental agents that influence epithelial barrier function, such as allergenic proteases, food additives or certain xenobiotics are reviewed in this paper. In addition, dietary factors that influence the allergenic response in a positive or negative way will be also described here. Finally, we discuss how the gut microbiota, its composition, and microbe-derived metabolites, such as short-chain fatty acids, alter not only the gut but also the integrity of distant epithelial barriers, focusing this review on the gut-lung axis.